ANTI-CORROSION PROPERTIES OF HEAVY OIL DEMULSIFIERS - SHYSHCHAK, MAKSYM; TOPILNYTSKYY, PETRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
One of the biggest challenges faced by the oil refining industry in the production, transportation, and processing of oil is the formation of oil-water emulsions and corrosion of oilfield equipment and pipelines caused by the impact of produced and transported media. This article presents the results of studies of the anticorrosive properties of the authors’ compositions of demulsifiers of the Dissolvan series manufactured by Clariant (Switzerland), which are designed to separate water-oil emulsions and are widely used in the oil industry. However, their effectiveness for heavy oils from Ukrainian fields has not been studied. For the study, we used heavy oil from the Bugruvatske field with a water content of 16 % by weight and a salt content of 12500 mg/l. Four of the twelve developed compositions were selected to determine the effect of demulsifiers on corrosion, which showed the highest degree of dehydration and demineralization in previous studies. The anticorrosive properties of the compositions were evaluated by the gravimetric method. It has been experimentally established that all the studied compositions reduce the corrosion rate and have a protective effect. Depending on the composition and the ratio of the components in it, corrosion processes are slowed down by 1.6-2.3 times, and the protective effect is within the range of 35-57%. The composition containing Dissolvan 3245, Dissolvan 4411, Dissolvan 5252, and Dissolvan 4064 demulsifiers showed the highest protective effect, and the lowest effect showed the industrial demulsifier Dissolvan 2830. The data obtained indicate the acute relevance of scientific research aimed at developing new effective reagents that can reduce losses from reagent shortages in the current economic environment. The results can be used for the reasonable development of a set of measures to increase production, rational transportation, and ways of further processing heavy oils from Ukrainian fields.